Optimalisasi Peringkat SERP Menggunakan Teknik White Hat SEO pada Industri Perhotelan - I Gede Sudiantara; Ni Made Erni Marlina Yani; I Made Dwi Putra Asana; I Wayan Adi Putra Yasa; I Putu Noven Hartawan (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
In today’s digital era, online visibility has become a critical factor for business success, particularly in the highly competitive hospitality industry. Premierplacehotels.com, despite offering quality services, experienced low search engine visibility, limiting its ability to attract organic traffic and direct bookings. Interview data revealed that online reservations were minimal at the beginning of 2024, with only three bookings in January, rising to 13 in February and 25 in March, highlighting the urgent need for an effective digital marketing strategy to enhance competitiveness. This study examines the implementation of White Hat Search Engine Optimization (SEO) techniques to improve the website’s performance on Search Engine Result Pages (SERPs). White Hat SEO focuses on ethical, long-term strategies in line with search engine guidelines, with methods applied including on-page optimization (such as improving meta tags and creating high-quality content) and off-page optimization (such as acquiring authoritative backlinks). The results demonstrate a significant improvement in keyword rankings, with “Juanda Airport Hotel” rising to position 3, “Surabaya Airport Hotel” to position 4, “Airport Hotel Juanda” to position 3, “Surabaya Hotel Near Airport” to position 3, “Hotel Near Juanda Airport Surabaya” to position 7, and “Airport Hotel Sidoarjo” to position 5. Website performance also improved, with clicks increasing from 321 to 560, impressions from 5,208 to 5,993, and the SEO health score from 68/100 to 83/100. In conclusion, the implementation of White Hat SEO proved effective in improving search visibility and website performance, offering a practical digital marketing strategy for enhancing competitiveness in the hospitality sector.